Development of sustainable logistics performance model using system dynamics in urban logistics service companies in Indonesia - Teuku Yuri M. Zagloel; M. Tirtana Siregar; Akhmad Hidayatno; Andri D. Setiawan (Cogent Business & Management, 2024)
The sustainable business model is critical in designing a performance model for logistics service companies by taking into account the dominant factors in managing all the resources needed to carry out operational processes, including the implementation of the logistics system as an effort to increase organizational competitiveness and resilience in the logistics services industry in a sustainable manner. The problems faced today are in line with the increasing frequency of using logistics services with the growth of E-commerce so the competition for logistics services companies, especially in urban areas, is getting tighter. This study used Mix Methods Research (MMR) with an explanatory design strategy and Structural Equation Model-Partial Least Square (PLS) analysis. In this study, a measurement model simulation used a system dynamic approach. Previous studies used the variant-based structural equation method but were limited to 1st-order models. This study aimed to formulate a more comprehensive sustainable logistics management model using the 2nd-order model and continued with a measurement model simulation up to 2040. The population in the study were employees of urban logistics services companies at the supervisor level with more than 5 years of service. Data were collected through questionnaires, observation, Focus Group Discussion (FGD), and literature study from January to August 2023. Based on the results, economic factors, environmental factors, social factors, and customer factors had a positive influence of 13.8 % (0.138 100%), 12.9 % (0.129 100%), 14.2 % (0.142 100%) and 12.9% (0.129 100%), respectively, meaning mutual support to the sustainable logistics model. Based on dynamic system analysis, the sustainable logistics model will have an increasing valuation every year. Thus, the relationship between variables in the sustainable logistics model was good in maintaining the company sustainability. This study is expected to give an exact recommendation for logistics companies to maintain their sustainability by always improving the four main factors with the positive influence namely environmental, customer, social, and economic factors.
Keywords: 650; logistic; mixed method; partial least square; sustainable model; system dynamic; urban courier